Selection of New Study Programs Based on Prospective Students’ Expectations and University Considerations Using AHP Approach - Ferdinan, Bernardus Aris; Dewantoro, Albertus Daru; Nugroho, Robertus Adi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Education is one of the important factors that need to be considered in improving the quality of human resources. Management of formal education is an important key in maximizing the potential of human resources. One of the educational institutions that play a huge role in increasing this potential in Higher Education Institutions. Parts of the efforts made in an effort to improve the quality of higher education is to provide a platform for students to choose to in higher education. This research seeks to explore and analyze the study interests of prospective students in Surabaya. By using the Analytical Hierarchy Process (AHP) to describe the needs of study programs according to market needs and interests, this article seeks to show from a scientific point of view how students are interested in entering study programs in this era. This provides opportunities for universities to consider opening new study programs in the future.